2020
DOI: 10.1080/07352166.2020.1742578
|View full text |Cite
|
Sign up to set email alerts
|

Political fragmentation and economic growth in U.S. metropolitan areas

Abstract: This paper analyzes the impact of local political fragmentation on population, employment, and per capita money income growth in 314 U.S. metropolitan areas. The results are mixed. Smaller central cities and more special district overlap are important for population growth. The findings do not generalize to employment or per capita money income growth. These findings mask important regional variation: political fragmentation is largely unrelated to economic growth in Midwestern and Western metropolitan areas. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
(87 reference statements)
0
13
0
1
Order By: Relevance
“…The general assumption behind this trend is that local governments have a better understanding of the local needs (Tiebout, 1956[15]; Oates, 1999 [16]; Klugman, 2013[17]). The same argument underlies the concepts of place-based policies (Barca, 2009[18]; Barca, Mccann and Rodríguez-Pose, 2012 [19]) and smart-specialisation (McCann and Ortega-Argilés, 2015 [20]; Foray, 2015 [21]).…”
Section: General Debates On Decentralisationmentioning
confidence: 88%
“…The general assumption behind this trend is that local governments have a better understanding of the local needs (Tiebout, 1956[15]; Oates, 1999 [16]; Klugman, 2013[17]). The same argument underlies the concepts of place-based policies (Barca, 2009[18]; Barca, Mccann and Rodríguez-Pose, 2012 [19]) and smart-specialisation (McCann and Ortega-Argilés, 2015 [20]; Foray, 2015 [21]).…”
Section: General Debates On Decentralisationmentioning
confidence: 88%
“…State-level analyses conducted by Akai and Sakata (2002) and Akai, Nishimura and Sakata (2007) in the United States have produced evidence that fiscal decentralization is positively related to economic growth. From a broader local government fragmentation perspective, other studies have found empirical connections between decentralized governance and economically related growth and activities (Hatfield and Kosec 2013; Goodman 2021; Stokan and Deslatte 2019). The findings of Stokan and Deslatte (2019) specifically show a negative relationship between state-imposed tax and expenditure limits (TELs) and economically driven tax abatements.…”
Section: Political Transaction Costs State Interventions and Municipa...mentioning
confidence: 99%
“…Special districts have proliferated rapidly since the 1970s and driven the fragmented local landscape of the U.S. special districts that are created for various reasons, such as general‐purpose governments’ circumvention against state fiscal limitations (Carr and Farmer 2011; Billings and Carroll 2012), cost‐management of local service (Park and Park 2021), extension of public service provision at the remote areas (Frant 1997), and meeting overall service demand (McCabe 2000). Consequences of special district creation include higher debt burdens of overlapping governments than permitted level (Greer, Moldogaziev, and Scott 2018), larger government with regards to public employment, revenue, and spending level (Berry 2008; Schneider 1989), population growth (Goodman 2020), and lower service quality despite higher service cost (Berry 2009).…”
Section: Literature Reviewmentioning
confidence: 99%